2016
DOI: 10.3389/fnsys.2016.00082
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Combining rTMS with Behavioral Therapy

Abstract: Upon its inception, repetitive transcranial magnetic stimulation (rTMS) was delivered at rest, without regard to the potential impact of activity occurring during or around the time of stimulation. rTMS was considered an experimental intervention imposed on the brain; therefore, the myriad features that might suppress or enhance its desired effects had not yet been explored. The field of rTMS has since grown substantially and therapeutic benefits have been reported, albeit with modest and inconsistent improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…This would include well-defined stimulation parameters [ 49 ], a well-defined and reproducible behavioral intervention, and a well-characterized and (ideally) homogenous patient group. The details of the relationship of neuromodulation to the behavioral therapy should also be considered in the experimental design and reported [ 175 ]. Given that inter-individual variability in response to neuromodulation is a clear issue [ 176 , 177 ], it is possible that mean group differences may not show an effect, but that careful patient characterization may identify predictors (e.g.…”
Section: Clinical Trial Design and Implementationmentioning
confidence: 99%
“…This would include well-defined stimulation parameters [ 49 ], a well-defined and reproducible behavioral intervention, and a well-characterized and (ideally) homogenous patient group. The details of the relationship of neuromodulation to the behavioral therapy should also be considered in the experimental design and reported [ 175 ]. Given that inter-individual variability in response to neuromodulation is a clear issue [ 176 , 177 ], it is possible that mean group differences may not show an effect, but that careful patient characterization may identify predictors (e.g.…”
Section: Clinical Trial Design and Implementationmentioning
confidence: 99%
“…Moreover, non-invasive brain stimulation techniques including rTMS exert effects on cognitive functions that psychotherapy may rely on, such as explicit learning or top-down emotional control [24]. In neurorehabilitation, combined application of rTMS and cognitive rehabilitation therapies has been shown to result in beneficial effects [25], mainly in the motor [26] and language domain [27,28] as well as unilateral neglect [29]. A similar effect may apply to the behavioral effect of rTMS þ PT in psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…This because brain state manipulations may act as a functional priming of a certain neurocircuitry, which, consequently, may respond differently to neurostimulation (Silvanto et al, 2017). Furthermore, functional engagement of a neurocircuitry with a cognitive task has been proposed to facilitate the long-term potentiation like-effects induced by NIBS (Luber et al, 2007;Tsagaris et al, 2016). Otherwise, when NIBS is applied before or simultaneously to a cognitive or behavioral intervention, it may enhance and facilitate inherent learning processes associated with these interventions, considering the ability of NIBS in boosting DA signaling and the evidences suggesting that strengthening the DA signal may improve memory formation, as well as emotionally relevant information encoding (Cannizzaro et al, 2019).…”
Section: Combining Cognitive Training/therapy With Nibsmentioning
confidence: 99%
“…However, the temporal relationship between multimodal interventions remains relatively an unexplored territory (Tsagaris et al, 2016), and is one of the most poorly reported variables in NIBS studies, although identifying the optimal timing of combined interventions may enhance their therapeutic effects, while also helping to avoid inducing maladaptive plasticity.…”
Section: Combining Cognitive Training/therapy With Nibsmentioning
confidence: 99%